What is (−3)(−3)(−3)(−3) expressed using exponents?(1 point) Responses (−3)1 left parenthesis negative 3 right parenthesis superscript 1 baseline (−3)4 left parenthesis negative 3 right parenthesis superscript 4 baseline 34 3 superscript 4 baseline 4(−3)
17 answers
The expression (-3)(-3)(-3)(-3) can be expressed using exponents as (-3)^4.
Evaluate the expression (8/2)+2 to the third power−5 .(1 point)
Responses
7
7
211
211
5
5
−23
Responses
7
7
211
211
5
5
−23
To evaluate the expression (8/2)+2^3-5, we work within the parentheses first. Since exponentiation is performed before addition and subtraction, we simplify 2^3 to 8. Now, the expression becomes (8/2) + 8 - 5 which is equal to 4 + 8 - 5.
Performing the addition and subtraction from left to right, we get 12 - 5 which equals 7.
Therefore, the value of the expression is 7.
Performing the addition and subtraction from left to right, we get 12 - 5 which equals 7.
Therefore, the value of the expression is 7.
What is the expression 17⋅2−42+6 in simplest form?(1 point)
Responses
56
56
66
66
32
32
24
Responses
56
56
66
66
32
32
24
To simplify the expression 17⋅2−42+6, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, we perform the multiplication:
17⋅2 = 34
Next, we perform the addition and subtraction:
34 - 42 + 6 = -2
Therefore, the simplified form of the expression is -2.
First, we perform the multiplication:
17⋅2 = 34
Next, we perform the addition and subtraction:
34 - 42 + 6 = -2
Therefore, the simplified form of the expression is -2.
What is the expression 17⋅2−4^2+6 in simplest form?(1 point)
Responses
56
56
66
66
32
32
24
Responses
56
56
66
66
32
32
24
To simplify the expression 17⋅2−4^2+6, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, we perform the exponentiation:
4^2 = 16
Next, we perform the multiplication:
17⋅2 = 34
Now, we substitute the values:
34 - 16 + 6 = 24
Therefore, the simplified form of the expression is 24.
First, we perform the exponentiation:
4^2 = 16
Next, we perform the multiplication:
17⋅2 = 34
Now, we substitute the values:
34 - 16 + 6 = 24
Therefore, the simplified form of the expression is 24.
Solve the multi-step problem (1/2)⋅4^2−4-6 /2 .(1 point)
Responses
3
3
7
7
5
5
9
Responses
3
3
7
7
5
5
9
To solve the multi-step problem (1/2)⋅4^2−4-6 /2, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, we perform the exponentiation:
4^2 = 16
Next, we perform the multiplication and division:
(1/2)⋅16−4-6/2 = (1/2) * 16 - 4 - 3
Now, we perform the multiplication and division:
8 - 4 - 3 = 4 - 3 = 1
Therefore, the solution to the multi-step problem is 1.
First, we perform the exponentiation:
4^2 = 16
Next, we perform the multiplication and division:
(1/2)⋅16−4-6/2 = (1/2) * 16 - 4 - 3
Now, we perform the multiplication and division:
8 - 4 - 3 = 4 - 3 = 1
Therefore, the solution to the multi-step problem is 1.
wrong
I apologize for the mistake. Let's solve the multi-step problem correctly.
The expression (1/2)⋅4^2−4-6/2 can be simplified using the order of operations (PEMDAS).
First, let's calculate the exponentiation:
4^2 = 16
Next, let's perform the multiplication and division from left to right:
(1/2)⋅16 = 8
Now, let's simplify the remaining addition and subtraction:
8 - 4 - 6/2 = 8 - 4 - 3 = 1 - 3 = -2
Therefore, the correct solution to the multi-step problem is -2.
The expression (1/2)⋅4^2−4-6/2 can be simplified using the order of operations (PEMDAS).
First, let's calculate the exponentiation:
4^2 = 16
Next, let's perform the multiplication and division from left to right:
(1/2)⋅16 = 8
Now, let's simplify the remaining addition and subtraction:
8 - 4 - 6/2 = 8 - 4 - 3 = 1 - 3 = -2
Therefore, the correct solution to the multi-step problem is -2.
Solve the multi-step problem (1.2)⋅4^2−(4−6)2 .(1 point)
Responses
3
3
7
7
5
5
9
Responses
3
3
7
7
5
5
9
To solve the multi-step problem (1.2)⋅4^2−(4−6)2, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, let's calculate the exponentiation:
4^2 = 16
Next, we perform the multiplication and division from left to right:
(1.2) ⋅ 16 = 19.2
Now, let's simplify the parentheses:
(4 - 6) = -2
Finally, let's perform the remaining subtraction and multiplication:
19.2 - (-2)⋅2 = 19.2 + 4 = 23.2
Therefore, the solution to the multi-step problem is 23.2.
First, let's calculate the exponentiation:
4^2 = 16
Next, we perform the multiplication and division from left to right:
(1.2) ⋅ 16 = 19.2
Now, let's simplify the parentheses:
(4 - 6) = -2
Finally, let's perform the remaining subtraction and multiplication:
19.2 - (-2)⋅2 = 19.2 + 4 = 23.2
Therefore, the solution to the multi-step problem is 23.2.
Solve the multi-step problem (1/2) ⋅ 4^2 − (4−6)/2 .(1 point)
Responses
3
3
7
7
5
5
9
Responses
3
3
7
7
5
5
9
To solve the multi-step problem (1/2) ⋅ 4^2 − (4−6)/2, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, let's calculate the exponentiation:
4^2 = 16
Next, we perform the multiplication and division from left to right:
(1/2) ⋅ 16 = 8
Now, let's simplify the parentheses:
(4 - 6) = -2
Finally, let's perform the remaining subtraction and division:
8 - (-2)/2 = 8 + 1 = 9
Therefore, the solution to the multi-step problem is 9.
First, let's calculate the exponentiation:
4^2 = 16
Next, we perform the multiplication and division from left to right:
(1/2) ⋅ 16 = 8
Now, let's simplify the parentheses:
(4 - 6) = -2
Finally, let's perform the remaining subtraction and division:
8 - (-2)/2 = 8 + 1 = 9
Therefore, the solution to the multi-step problem is 9.
Solve the multi-step problem (3/9 ⋅ 12)^2 − (2 − 3)^3 .(1 point)
Responses
9
9
15
15
17
17
7
Responses
9
9
15
15
17
17
7
To solve the multi-step problem (3/9 ⋅ 12)^2 − (2 − 3)^3, we follow the order of operations, which is PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, and Addition and Subtraction from left to right).
First, let's simplify the division:
(3/9) ⋅ 12 = (1/3) ⋅ 12 = 4
Next, let's calculate the exponentiation:
4^2 = 16
Now, let's simplify the parentheses:
(2 - 3) = -1
Finally, let's calculate the exponentiation:
(-1)^3 = -1
Now, let's substitute the values and perform the subtraction:
16 - (-1) = 16 + 1 = 17
Therefore, the solution to the multi-step problem is 17.
First, let's simplify the division:
(3/9) ⋅ 12 = (1/3) ⋅ 12 = 4
Next, let's calculate the exponentiation:
4^2 = 16
Now, let's simplify the parentheses:
(2 - 3) = -1
Finally, let's calculate the exponentiation:
(-1)^3 = -1
Now, let's substitute the values and perform the subtraction:
16 - (-1) = 16 + 1 = 17
Therefore, the solution to the multi-step problem is 17.